Bilinear approximations to the mixed-mode I-II delamination cohesive law using an inverse method - Morais, Alfredo
This paper presents an experimental and numerical study of the mixed-mode I-II delamination of unidirectional carbon/epoxy laminates. Double cantilever beam, end-notched flexure and mixed-mode bending tests were conducted in order to cover the full range of mode-mix combinations. Finite element cohesive zone models with a bilinear softening cohesive law were subsequently employed to fit experimental load-displacement curves. This required a genetic algorithm to find optimal bilinear softening parameters. Good agreement was achieved between predicted and experimental curves. Furthermore, the bilinear softening parameters showed consistent variations with the global mode-mix that could be interpreted in terms of local damage mechanisms. Nevertheless, further research is needed to define mixed-mode tractions and separations leading to a unique cohesive law.